Cross-Layer Optimization Performance of Single Cell Millimeter Wave OFDM Wireless Network Under Rain Fading - E. Endroyono; G. Hendrantoro; A. Matsushima (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2009)
This paper presents cross-layer optimization implementation for millimeter wave OFDM network in thepresence of rain fading. Cross-layer optimization is proposed to overcome the power inefficiency andcomplexity of conventional fading mitigation technique. The network is modeled as downlink multi-user singlecell OFDM network. The rain fading data is generated based on Synthetic Storm Technique using rain rate datameasured in Surabaya Area. To show the interest of cross-layer optimization, a combining optimization betweenphysical and MAC layer using dynamic sub-carrier allocation and adaptive power allocation algorithm isdemonstrated. The optimization objectives are the improvement of utility and fairness in heavily rain affectedcell. The result shows an improvement of utility for multi-user OFDM network in term of total rate.Keywords: OFDM, single cell multi-user, millimeter wave rain fading, SST, cross-layer design, JSPA.